Biodegradation of Carbofuran; A Review (Journal of Environmental Microbiology and Toxicology, 2020)
Pesticides are substances used for the destruction or control of pest. They include insecticides, herbicides, fungicides, rodenticides rats and mice, molluscides and others. Carbofuran is an insecticide that is very toxic pesticide often used to control pests in agricultural areas. Its usage is still being reported despite worldwide efforts to ban the pesticides. Reported deaths and illness due to indiscriminate and excessive use of carbofuran is still being reported in developing and third world countries prompting the call of more research on isolating microorganisms that are able to completely mineralize this toxic pesticide. The presence of toxic carbofuran in various soil types that can persist for many months can be remediated via the use of carbofuran-degrading microorganisms which is a more feasible and economical methods of remediation compared to various physicochemical methods. The aim of this review is to highlight the toxicity of carbofuran, especially in the Malaysian perspective and the current body of knowledge on carbofuran-degrading microorganisms that are able to remediate this toxic threat.
Keywords: Pesticides, biodegradation, carbofuran, bioremediation, Malaysia